Study the Effect of Welding Parameters on the Residual Stresses Induced by Submerged Arc Welding process - Amin, Samir Ali; Bakhy, Sadeq Hussein; Abdullah, Fouad Ali (Al-Nahrain Journal for Engineering Sciences, 2017)
Welding residual stress has influences on fatigue, fracture, and corrosion. It is therefore important to explore the welding factors effect on the residual stresses. In this work, four welding factors (current, arc voltage, welding travel speed and included angle) were used to weld low carbon steel (ASTM A516 Grade 60).The experiments included welding of (60) pieces with dimensions of (300 x 150) mm and 10 mm thickness that were conducted based on the design matrix founded by using design of experiment (DOE) software (DESIGN EXPERT 10) with response surface methodology (RSM) technique. The X-Ray diffraction (XRD) method was used to measure the residual stress, which was then modeled and optimized in terms of the welding factors using (RSM) technique. The data showed that the welding travel speed and arc voltage have a significant influence on the residual stress. It was found that the optimum solution for minimum residual stress was at 450 Amp welding current, 34 volt arc voltage, 38 cpm welding speed, and 60? included angle. Where, the optimum value of residual stress was (-88.4 MPa). Finally, the predicted and experimental results of residual stress were in agreement with a maximum error of 1.8%.